Business plan for a health club - Castelo, Rui Miguel André (2010)
This business plan describes all the steps and needs to build a health club in Faro. The fitness industry worldwide has showed a growing trend that in Portugal has been presented with a growing rate of 7,5% (Correia, 2006). The market penetration rate is of 5,7%, which represents 3350 potencial clients in Faro, being at the moment distributed by the 12 existing competitors, 2850 persons. The questionnaire showed that people go to the gym to get rid of stress, transform their body and to have qualified staff during workout. Cardiovascular machines, group classes and the indoor pool with hidromassage are the preferred activities in a gym. The Project has a duration of 120 months, with an investment of 600 thousand euros, with a break even period of 17 months and a 55 months paybak period. The NPV is 19842,13€ and the average annual rate of return during the 10 years period is 11,17%. The targeted segment are people above 45 years old, female, people that want to prevent diseases, get older later and transform their body. The main characteristics of the health club are the online gym, the indoor pool with hidromassage, steam room, a quality staff and complementary services (kids zone and laundry).